Effect of Land Use Land Cover on Soil Carbon Sequestration in Haliyal Taluka of Uttara Kannada District - Koppad, Arjun G.; Janagoudar, B. S. (Indian Forester, 2018)
The study was conducted in Haliyal taluka (15° 05' to 15° 25'N latitude and 74° 33' to 74° 57'E longitude) of Uttar Kannada district, Karnataka, India to assess the carbon sequestration in soils of different land use land cover classes. The IRS P6 LISS-III imageries were used and processed in ERDAS software with supervised classification identified based on ground truth data collected from different land use systems from GPS. The land use land cover classes were dense forest, horticulture plantation, sparse forest, agriculture land and open land. The soil samples up to one meter depth were drawn from different land use systems. Among the different land use classes, higher SOC was sequestered in Dense forest (184 t/ha) followed by horticulture plantation (144 t/ha). The SOC in sparse, open land and agriculture land was 110 t/ha, 106 t/ha and 74 t/ha respectively. The carbon mitigation potential of dense forest is 2.48 times higher compared to agricultural land followed by horticulture land (1.94 times).